(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
For chronic postoperative pain syndrome, the neuropathic component is a major component. The use of magnesium sulfate for the prevention of pain syndrome is theoretically based on its ability to block N-methyl-D-aspartate receptors in the spinal cord. Our aim was to evaluate the effect of magnesium sulphate as an adjuvant analgesic in the prevention of postoperative and chronic pain syndrome in patients after surgery using combined general anaesthesia.